FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPADATAN LALATDI DESA PURWODADI KECAMATAN MARGOYOSO KABUPATEN PATI - Chaca Ramadhani; Retno Hestiningsih; Nissa Kusariana (Jurnal Kesehatan Masyarakat (Undip), 2019)
There is a large-scale broiler farm close to the settlement in Purwodadi Village. Some people in Purwodadi Village raise livestock in the yard. According to previous research in Semarang, this could be factors of flies density in settlements. Based on results of preliminary survey there is many flies populations. Purpose of this research is determine the factors related to density of flies in Purwodadi Village. This type of research is analytical research with a cross sectional approach. Data is analyzed quantitatively. According to this research, variabel related to flies density are  temperature (p = 0.006), light intensity (p = 0.004), distance of house from broiler farm (p = 0.001), sanitation of residential facilities (p = 0.003) and the presence of livestock in the yard (p = 0.001). Variables that were not proven to be related to fly density were air humidity (p = 0.069) and wind speed (p = 0.600).